How Information Flows in Industrial Symbiosis (Circular Economy Value Chain) and What are the Gaps and Discontinuities? - Järvenpää Anne-Mari; Kantola Jussi; Salminen Vesa (United States, 2025)
The aim of circular economy is the efficient use of materials, but it is hampered by lack of information. Literature shows that lack of information causes challenges to close the waste loop. Developing material flows require understanding about the challenges between companies. Our research question is: How information flows in Industrial Symbiosis and what are the gaps and discontinuities? As industrial symbiosis, we mean business relation, where waste material is circulated as an input to another company. This paper presents a qualitative case study in Finland with three cases with different material flow: biowaste, glass waste and e-waste. We noticed that the reason why accurate information is not shared, might relate to the information systems that company are using, as they might give estimations only in the meetings held quarterly, or they forget to inform other company of it. Another reason might be the business model, as the waste material using company might buy the material.
Keywords: Industrial symbiosis, Circular economy, Information flow
Human Factors, Business Management and Society